1759 metų “Ziwato” o, i̯o, ii̯o kamienų daiktavardžiai ir jų raida - Vaičiakauskytė, Sonata (Kalbotyra, 2001)
The article analyses o-, i̯o-, ii̯o-stem nouns in “Ziwatas” (1759) and their evolution, comparing with the modern system of noun inflexion in the western subdialect of the North Žemaitian dialect of Kretinga. The analysis showed that in the middle of the 18th century there had already occurred a shortening of singular locative case. May be at the “Ziwatas” time nasal vocal -ų was pronounced in the plural genitive stressed ending. At the end of the 18th century shortened plural dative endings were already used.